Neutrophils at the crossroads of innate and adaptive immunity - Rosales, Carlos (Journal of leukocyte biology, 2020)
Neutrophils are the most abundant leukocytes in blood. From the circulation, they are quickly mobilized to sites of inflammation and/or infection. At the affected tissues, neutrophils display an impressive array of antimicrobial functions, including degranulation, production of reactive oxygen species (ROS), phagocytosis, and formation of neutrophil extracellular traps (NET). Because neutrophils are the first type of leukocytes to arrive at affected tissues and display potent microbicidal functions, they have been classically viewed as the first line of defense. In this view, neutrophils only destroy invading pathogens and then quietly die at the site of infection. However, in the last decade it has become increasingly evident that neutrophils are much more complex cells having not only effector functions in the innate immune response, but also the capacity of modulating the adaptive immune response, via direct interaction with, or by producing cytokines that affect dendritic cells and lymphocytes. In addition, neutrophil heterogeneity with clear different functional phenotypes has been recently described particularly in cancer and inflammation. This review provides an overview on the life of a neutrophil describing its beginnings, lifespan, and their principal functions in innate and adaptive immunity. Also, neutrophil heterogeneity and our current understanding of neutrophil contributions to health and disease are discussed. Review on neutrophils as important effector cells of both innate and adaptive immunity.